A SOCIOPRAGMATIC COMPARISON OF TABOO WORDS USE IN TENGANAN PEGRINGSINGAN AND DENPASAR - I Made Astu Mahayana; I Made Netra; I Wayan Simpen; I Gusti Ayu Gde Sosiowati (Indonesian EFL Journal, 2025)
This study explores the sociopragmatic functions of taboo language in two contrasting Balinese speech communities: Tenganan Pegringsingan Village and Denpasar City. Using a qualitative descriptive approach supported by non-participant observation, semi-structured interviews, and discourse documentation, the research examines how speakers employ taboo expressions to negotiate politeness, express emotion, and perform social identity. Grounded in Brown and Levinson’s Politeness Theory (1987), Locher and Watts’s concept of relational work (2005), and Culpeper’s notion of impoliteness (2011), the analysis reveals a clear sociocultural divergence. In Denpasar, taboo words function as expressive and relational tools that reinforce solidarity, humor, and affective intensity within peer-based interactions. In contrast, Tenganan’s linguistic norms constrain the use of taboo expressions to maintain ritual purity, respect, and social hierarchy. Componential analysis further uncovers that Denpasar’s taboo lexicon emphasizes emotional intensity and pragmatic versatility, while Tenganan’s reflects moral restraint and symbolic caution. The findings demonstrate that taboo language, far from being mere linguistic deviance, operates as a culturally situated pragmatic resource that mirrors each community’s values, power dynamics, and communicative ideologies.